Design Calculations and Experimental Analysis of “Over Roof Solar Chimney” - Nurhusna Bt Yusoff , Nurhusna (2008)
This project analyses the mechanism behind a solar chimney to generate sufficient power to sustain a single home and is more directed towards the analytical and experimental aspect of the analysis.